2019
DOI: 10.1016/j.ijheatmasstransfer.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The petal effect of parahydrophobic surfaces offers low receding contact angles that promote effective boiling

Abstract: Despite extensive study of boiling processes and their widespread use in industry, critical interactions between the fluid and surface during boiling remain poorly understood. Simplistic, static descriptions of the contact angle are still relied upon to describe the effects of surface wettability on dynamic interfacial processes that govern boiling. This work demonstrates the critical role of the dynamic wettability characteristics of a surface on bubble growth dynamics and boiling performance. In spite of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…In particular, at the bottom of the sample where the "holes" density is higher, the receding contact angle is the lowest and the surface resulted to be flooded by the condensate. This is in agreement with several studies reported in literature [34,35] that demonstrated how the surface wettability is mostly influenced by the receding contact angle. Due to small dimension of the "holes", in loco analysis was not possible to be done, but correlating the results with a bare aluminum sample tested in the same experimental conditions, it is reasonable to suppose the formation of aluminum hydroxide at the bottom of the "holes" or the exposure of bare Aluminum due to coating's removal (See Figures S5 and S6).…”
Section: Dwc Evolutionsupporting
confidence: 94%
See 1 more Smart Citation
“…In particular, at the bottom of the sample where the "holes" density is higher, the receding contact angle is the lowest and the surface resulted to be flooded by the condensate. This is in agreement with several studies reported in literature [34,35] that demonstrated how the surface wettability is mostly influenced by the receding contact angle. Due to small dimension of the "holes", in loco analysis was not possible to be done, but correlating the results with a bare aluminum sample tested in the same experimental conditions, it is reasonable to suppose the formation of aluminum hydroxide at the bottom of the "holes" or the exposure of bare Aluminum due to coating's removal (See Figures S5 and S6).…”
Section: Dwc Evolutionsupporting
confidence: 94%
“…Similar degradation trends with time have already been found for other coatings [34], meaning that coatings change over time due to the harsh environment of the condensation experiments. In particular, such high temperatures (around 100 • C) of saturated steam induce shrinkage of the sol-gel treatments, as reported in [31].…”
Section: Dwc Evolutionsupporting
confidence: 80%
“…Surfaces exhibiting the petal effect have been proposed for separation processes and collection of water via directional liquid transport . It has also been recently demonstrated that parahydrophobic surfaces are ideal for facilitating bubble nucleation and departure during boiling . Models of the wetting state are typically used to design surface topologies that provide the desired wetting characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…The growth characteristics are also similar to those reported on hydrophilic surfaces (surfaces with low receding contact angles). 65 , 66 The bubble first experiences a fast growth process, e.g., 0–6, 0–3, and 0–2 ms on SS, CPF-1, and SPF-2, respectively. The bubble then shows a quick shrinking process of the gas–liquid–solid phase line because buoyancy begins to distort the bubble shape.…”
Section: Resultsmentioning
confidence: 99%